Role of GIS in School Geography - Pandey, Aparna (JOURNAL OF INDIAN EDUCATION, 2011)
GIS is a fast developing area with vast potentiality for geography education. Since it is based on inquiry based learning it ignites young minds in exploring the world around them. While GIS is rooted to geography, it’s strong linkage to mathematics and statistics help in developing analytical skills. For last more than one decade, the NCERT has made efforts continuously to strengthen school geography curriculum by including GIS at higher secondary stage (NCFSE -2000 and NCF-2005) and by providing in-service training in GIS to geography teachers, regularly from 2008. There is a need to make concerted efforts at all levels to improve its visibility in educational institutions for better application. With adequate training, analysis and interpretation of spatial data it would be much easier and interesting for students and teachers as well.